Emergence of staphylococcal scalded skin syndrome associated with a new toxinogenic, methicillin‐susceptibleStaphylococcus aureusclone. Issue 1 (January 2019) - Doudoulakakis, Anastassios; Spiliopoulou, Iris; Syridou, Garyfallia; Giormezis, Nikolaos; Militsopoulou, Maria; Lebessi, Evangelia; Tsolia, Maria
Abstract : N/A: A sharp increase in staphylococcal scalded skin syndrome (SSSS) cases has been recorded in our settings since 2015, with 31 cases having been documented during the period 2014–2017. The molecular investigation of strains from the above period showed the emergence of a methicillin‐susceptible, mupirocin‐ and fusidic acid‐resistant Staphyloccocus aureus clone that belongs to the ST121 complex and carries both epidermolysin ( eta/etb ) genes. We concluded that the SSSS caused by the newly emerged, highly virulent community‐associated‐methicillin sensitive S. aureus strains that have been encountered lately is more severe than impetigo. Physicians should be aware of the probability of SSSS epidemics from strains that are resistant to mupirocin and fusidic acid, which have been used irrationally and excessively.